2017
DOI: 10.18632/aging.101268
|View full text |Cite
|
Sign up to set email alerts
|

p16(Ink4a) and senescence-associated β-galactosidase can be induced in macrophages as part of a reversible response to physiological stimuli

Abstract: Constitutive p16Ink4a expression, along with senescence-associated β-galactosidase (SAβG), are commonly accepted biomarkers of senescent cells (SCs). Recent reports attributed improvement of the healthspan of aged mice following p16Ink4a-positive cell killing to the eradication of accumulated SCs. However, detection of p16Ink4a/SAβG-positive macrophages in the adipose tissue of old mice and in the peritoneal cavity of young animals following injection of alginate-encapsulated SCs has raised concerns about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
231
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(245 citation statements)
references
References 75 publications
13
231
0
1
Order By: Relevance
“…2C). The residual p53 expression in Adipoq-p53iKO mice may reflect the reported increases of p53 in adipose progenitor cells, macrophages, and endothelial cells (26,35,36), which are not affected by Adipoq promoter-driven Cre expression in differentiated adipocytes (38). RT-qPCR also confirmed reduced expression levels of known p53 target genes [Cdkn1a (or p21), Tigar, and Bax] in aged iWAT of Adipoq-p53iKO mice, compared to the control (Fig.…”
Section: Increased P53 Expression and Impaired Beige Adipocyte Recruimentioning
confidence: 72%
See 1 more Smart Citation
“…2C). The residual p53 expression in Adipoq-p53iKO mice may reflect the reported increases of p53 in adipose progenitor cells, macrophages, and endothelial cells (26,35,36), which are not affected by Adipoq promoter-driven Cre expression in differentiated adipocytes (38). RT-qPCR also confirmed reduced expression levels of known p53 target genes [Cdkn1a (or p21), Tigar, and Bax] in aged iWAT of Adipoq-p53iKO mice, compared to the control (Fig.…”
Section: Increased P53 Expression and Impaired Beige Adipocyte Recruimentioning
confidence: 72%
“…Like the WAT, p53 also increased in interscapular brown adipose tissue (iBAT; data not shown). It has been reported that p53 expression increases in macrophages and endothelial cells in aged tissues (35,36). To confirm p53 increased in adipocytes of aged iWAT/eWAT, we isolated SVF from iWAT of young and aged mice and examined p53 expression in cultured adipocytes differentiated in vitro.…”
Section: Increased P53 Expression and Impaired Beige Adipocyte Recruimentioning
confidence: 99%
“…Macrophages have been reported to express high levels of p16 INK4a and senescent‐associated β ‐galactosidase activity (Hall et al, 2017). Although p19 ARF expression in macrophages has not been documented, and no luciferase activity was detected in the BALF cells of ARF‐DTR mice (Hashimoto et al, 2016), it is still possible that DT acted through the macrophage depletion in PPE‐treated ARF‐DTR mice.…”
Section: Resultsmentioning
confidence: 99%
“…Conditions that trigger senescence include genomic instability, extreme telomere shortening, metabolic and proteostatic stress, reactive oxidative species (ROS), oncogene activation, mitochondrial dysfunction, epigenetic changes, and other mechanisms that have not been fully clarified (Childs, Durik, Baker, & van Deursen, ; Childs et al, ; López‐Otín et al, ). In general, these conditions trigger a response that activates the tumor suppressor genes p53, p16 Ink4a , and p21 that utilize different pathways to induce cell cycle arrest (Hall et al, ; Liu et al, ). Most studies indicate that senescence‐induced replication arrest acts as a tumor suppression mechanism, but other physiological roles are emerging, including fetal organ development, wound healing, and aging (Baker & Petersen, ; Pratsinis, Mavrogonatou, & Kletsas, ; Wiley & Campisi, ; Zhang, Chen, Liu, Chen, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%